A Bibliometric Analysis of Publications On "Teaching Philosophy"- Based On Web of Science Database From 2000 To 2023. - Poologanathan, P.; Anitha, R. (Central Library, Thiruvaroor, TamilNadu, 2024)
Bibliometric analysis is a quantitative research method used to analyze and evaluate scholarly literature in the context of academic and scientific research. It involves the systematic analysis of patterns, relationships, and characteristics of bibliographic data, such as citations, publications, and other metadata related to academic papers, journals, authors, published countries, important keywords and research fields. Bibliometric analysis can provide valuable insights into the productivity, impact, and trends within a particular field of study. The following are some key components and applications of bibliometric analysis such as, citation analysis, author and journal productivity, co-authorship and collaboration, research topics and trends, journal impact factors, institutional analysis, evaluation of researchers, scientific mapping and evaluation of research grants. A teaching philosophy is most productivity research area in the fields of philosophy and educations in the current scenario. Teaching philosophy refers to a guiding statement that outlines an educator's beliefs, principles, and approach to teaching and learning. It reflects A Bibliometric Analysis of Publications...... their pedagogical values, goals, and the methods they use to engage and educate students. Teaching philosophies most widely based on individual experiences, educational contexts, and personal beliefs. Followings are some key features of teaching philosophy, educational goals, teaching methods, learning environment, assessment and feedback, role as an educator, beliefs and values, reflection and improvement, communication and adaptability. The main purposes of this study to analysis the literature trends on the publications in the teaching philosophy, which were indexed in web of science multidisciplinary citation database. It provides the access to a vast collection of scholarly articles, conference proceedings, and other research materials.